2003
DOI: 10.1242/jeb.00614
|View full text |Cite
|
Sign up to set email alerts
|

Time-course of the effect of dietaryl-tryptophan on plasma cortisol levels in rainbow troutOncorhynchus mykiss

Abstract: SUMMARYIsolated juvenile rainbow trout were fed a feed supplemented with l-tryptophan (TRP) for 3, 7 or 28 days, after which they were either sampled directly (undisturbed) or subjected to a standardised stressor prior to sampling. Controls (stressed and undisturbed) received the same feed but without any supplementary TRP. Stress resulted in a significant elevation of plasma [cortisol] in fish fed control feed and in fish fed TRP-supplemented feed for 3 and 28 days. However, fish fed TRP-supplemented feed for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
89
1
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(109 citation statements)
references
References 47 publications
(33 reference statements)
12
89
1
1
Order By: Relevance
“…For example, dietary Trp affected 5-HT turnover significantly in the hypothalamus (7) and optic tectum (8) 1 d post Trp treatment, whereas this effect of dietary Trp was expressed less in the brain stem and telencephalon. Moreover, Basic et al (15) showed that Trp treatment tended to enhance hypothalamic 5-HT 1 d post Trp, and that this effect was not present 10 d post Trp treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, dietary Trp affected 5-HT turnover significantly in the hypothalamus (7) and optic tectum (8) 1 d post Trp treatment, whereas this effect of dietary Trp was expressed less in the brain stem and telencephalon. Moreover, Basic et al (15) showed that Trp treatment tended to enhance hypothalamic 5-HT 1 d post Trp, and that this effect was not present 10 d post Trp treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary manipulations have been used as tool to investigate the involvement of brain 5-HT in behaviour, mood and cognition in humans (3) . Such manipulations have also been shown to affect the endocrine and behavioural response to stress in comparative vertebrate models (4)(5)(6)(7)(8) . Many of these effects have been attributed to the immediate precursor of 5-HT, the essential amino acid tryptophan (Trp), which enters the brain from the circulation in competition with other large amino acids (LNAA) (9) .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Functional amino acids could be used to design balanced aquafeeds to enhance the efficiency and profitability of global aquaculture production [9]. Furthermore, we tested the same dosages and administration time that those used previously in other fish species [17][18][19][20][21][22].…”
Section: Resultsmentioning
confidence: 99%
“…Hseu et al, 2003 found that dietary supplementation of L-tryptophan in juveniles rainbow trout diet leads to inhibit aggression behavior. Hoglund, Sorensen, Bakke, Nilsson, & Øverli, 2007 also revealed that L-tryptophan reduce cannibalism and stress induced anorexia in juvenile grouper and Lepage, Vilehez, Pottinger and Winberg, (2003) showed that it prevents stress induced cortisol surge. In contrast, Krol, Flisiak, Urbanowicz, and Ulikowski, (2014) reported that the tryptophan supplementation had no significant effect on growth or survival of Silurus glanis.…”
Section: Discussionmentioning
confidence: 98%